Source Based Waste Management at the Environment Department of Buleleng Regency - Luh Gede Eka Yanthi; Putu Indah Rahmawati; Ni Made Ary Widiastini (Budapest International Research and Critics University, 2022)
This study aims to determine the management of waste management organized by the Buleleng Regency Environmental Service and to explore information related to problems that occur in the implementation of waste management, especially source-based waste management organized by the Buleleng Regency Environmental Service. This study uses descriptive qualitative analysis as a research methodology. The data collected was obtained through observation of documents and reports, in-depth interviews, focus group discussions. Observation of data and reports, in-depth interviews and focus group discussions were conducted to obtain data related to waste management at the Buleleng Regency Environmental Service with sources namely officials Structural and Environmental Extension Officer at the Buleleng Regency Environmental Service. The results showed that the general waste management and source-based waste management organized by the Buleleng Regency Environmental Service were not optimal, both in terms of waste reduction and handling activities. The researcher found that from the waste balance report compiled every semester from 2019 to 2021, there was a gap between the achievements and the targets set in the Strategic Policy for the Management of Household Waste and Waste Similar to Household Waste (Jakstrada). Waste management activities are more focused on waste handling